PROTOTYPE DESIGN OF HONEY EXTRACTOR MACHINE USING ARDUINO MICROCONTROLLER WITH INTERNET OF THINGS (IOT) MODEL - Swastika, Rulin; Rohman, Efi; Al Khoir, M. Agus Badruzaman; Nuziar, Alfian (Jurnal TAM (Technology Acceptance Model), 2022)
The application of appropriate technology based on the Adruino Uno R3 Microcontroller using the Android Operating System has been tested in this research. Sensor technology coupled with Arduino is applied to control the electric motor mounted on the honey bee extractor. It is proven that this can increase harvest efficiency because honey bees can produce directly without building a honeybee nest, which takes 14 days. In addition to time efficiency, the extractor processing process is also more efficient and optimal because all the honey in the hive is removed maximally without damaging the honeybee nest structure. A honey extractor is a tool used to squeeze honeycomb which has been produced by bees and has a high economic value